Survey of cultivated and wild edible plant species used in the Department of Choco, Colombia - Medina, M.A.=700 1 Mena, A.; Prohens, J.
(En, Fr, Es)
ilus., 11 ref.
Keywords: CULTIVOS ALIMENTICIOS; VARIEDADES; ESPECIES; ETNOBOTANICA; COLOMBIA